Tillering of two wheat genotypes as affected by phosphorus levels - doi: 10.4025/actasciagron.v34i3.13326 - Fioreze, Samuel Luiz; Castoldi, Gustavo; Pivetta, Laércio Augusto; Pivetta, Laerte Gustavo; Fernandes, Dirceu Maximino; Büll, Leonardo Theodoro (Acta Scientiarum. Agronomy, 2011)
Tillering plays an important role in wheat yield potential and it is affected by genotype and environmental conditions. This work aimed to study the effects of phosphorus levels on tiller emergence, survival and contribution to yield potential of two wheat cultivars. The experiment was carried out under greenhouse conditions in Botucatu, São Paulo State, Brazil. A 2 x 5 factorial randomized block design with four replications was applied. Two wheat cultivars (IAC 370 and IAC 375) and five phosphorus levels (0, 150, 300, 450 and 600 mg dm-3) were evaluated in pots with 10 dm3 of a clayey Oxisol. Higher P levels increased tiller emergence, survival and yield, especially for secondary tillers. Tiller abortion levels were higher in IAC 370 cultivar whereas retention of formed tillers was higher in IAC 375.